Payment System for Official Travel Expenses at the Office of the Jeneberang Saddang River Basin and Protected Forest Management Center - Muhammad Asir; Dewi Puspitasari; Rahmi Rahmi; Annisa Ishmat Asir (PINISI Discretion Review, 2022)
Efforts to expedite the financial administration of an office certainly require a good payment system. An efficient payment system certainly realizes the implementation of financial administration that is able to facilitate every activity. The purpose of the study was to determine the payment system for the Jeneberang Saddang River Basin and Protected Forest Management Center (Indonesia: Balai Pengelolaan Daerah Aliran Sungai dan Hutan Lindung Jeneberang Saddang / BPDASHL). The research approach uses descriptive qualitative. The financial administration management of business travel applies two payment systems, namely the first official travel payment system is the Lumpsum payment system where employees traveling on business will receive a certain amount of money which is paid at once. And the second is the At-Cost System where employees take official trips and receive a certain amount of money in accordance with the available evidence and must follow procedures that are in accordance with their respective official travel expense payment systems so that official trips run effectively and efficiently.